Estudo fitoquímico e investigação das propriedades antimicroniana e inseticida de annona montana (annonaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The species Annona montana belongs to the Annonaceae family and is popularly known as “araticum” or “false soursop”. In the regions where it is endemic, it has been used as a phytotherapeutic agent for the treatment of various diseases. The observation of the close relationship between the ethnomedicinal use and the production of chemical compounds from species of this family motivated the isolation of secondary metabolites with pharmacological properties such as cytotoxic, antiparasitic, larvicidal and anticoagulant. Therefore, this work aims to study the phytochemical and biological properties of A. montana. For this purpose, extractions with different solvents (hexane, ethanol and methanol) were performed from the dried and ground trunk. The methanolic extract of the heartwood was subjected to conventional acid-base treatment. The ethanolic extract of the trunk bark was partitioned into liquids. Both were subjected to the chromatographic fractionation process using different stationary phases and eluent gradients of increasing polarity, resulting in the isolation of two known alkaloids. The alkaloid fraction of the methanolic extract resulted in the isolation of the alkaloid with oxoaporphinic skeleton called liriodenine. From the ethyl acetate fraction of the ethanolic extract, the alkaloid with pyrimidine-β-carboline skeleton called annonmontine was isolated. Nuclear Magnetic Resonance Spectroscopy (1H and 13C NMR, one- and two-dimensional) and Mass Spectrometry (MS) were used for structural elucidation. The crude extracts, fractions and isolated substances were subjected to evaluation of antimicrobial and insecticidal activity against Aedes aegypti. The results obtained demonstrated that the alkaloid and neutral fractions presented significant antimicrobial activity against Klebsiella pneumoniae, forming translucent inhibition halos measuring between 20 and 30 mm, respectively. In the evaluation of larvicidal activity, the neutral fraction presented a LC50 of 3.6 µg/mL, being capable of killing 100% of the larvae after 48 h. The alkaloid fraction, LC50 of 7.9 µg/mL, with mortality of 90% of the larvae in the same time. Annonmontin, one of the isolated compounds, proved to be effective in the mortality of adult insects of A. aegypti.
Keywords: .; CIENCIAS EXATAS E DA TERRA; Metabólitos secundários; Cromatografia; Atividade larvicida; Alcaloides